2020
DOI: 10.3389/fvets.2020.00168
|View full text |Cite
|
Sign up to set email alerts
|

Endemic and Emerging Arboviruses in Domestic Ruminants in East Asia

Abstract: Epizootic congenital abnormalities caused by Akabane, Aino, and Chuzan viruses have damaged the reproduction of domestic ruminants in East Asia for many years. In the past, large outbreaks of febrile illness related to bovine ephemeral fever and Ibaraki viruses severely affected the cattle industry in that region. In recent years, vaccines against these viruses have reduced the occurrence of diseases, although the viruses are still circulating and have occasionally caused sporadic and small-scaled epidemics. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 267 publications
0
29
0
Order By: Relevance
“…In recent years, more and more novel arboviruses have been identified from various vector hosts [ 10 , 11 ]. Additionally, a growing number of novel TBVs were also discovered throughout the world, for instance, BRBV in USA [ 4 ], ALSV in China [ 5 ], Hunter island group virus (HIGV) in Australia [ 12 ], Muko virus (MUV), and Tarumizu tick virus (TarTV) in Japan [ 13 , 14 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more novel arboviruses have been identified from various vector hosts [ 10 , 11 ]. Additionally, a growing number of novel TBVs were also discovered throughout the world, for instance, BRBV in USA [ 4 ], ALSV in China [ 5 ], Hunter island group virus (HIGV) in Australia [ 12 ], Muko virus (MUV), and Tarumizu tick virus (TarTV) in Japan [ 13 , 14 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, the awareness of BEFV prophylaxis gained attention. Although a few BEFV vaccines are now available commercially, they revealed only limited effectiveness [15]. A few inactivated vaccines showed high neutralizing antibody titers to BEFV challenge, but failed to trigger effective cell-mediated immune (CMI) responses [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested BEFV to possess high substitution rates (Trinidad et al 2014 ). However, few recent reports on the generation of novel genogroups with higher viral virulence (Yanase et al 2020 ) and limited vaccine effectiveness suggest BEFV evolution is enhancing variant's fitness landscape to help overcome the host immune system (Aziz-Boaron et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The new geographical expansions with enhanced case fatality rate and high production losses alarm BEFV as an evolving arbovirus that warrants closer scrutiny in surveillance, epidemiology, and ecological impact (Lee 2019 ; Yanase et al 2020 ). Despite the multiple decades of episodic reporting on seasonal incursions from many South Asian countries, including India (Nandi and Negi 1999 ; Walker and Klement 2015 ), no complete sequence information was available until recently (Pyasi et al 2020 ), which hinders progress for its detection and prevention.…”
Section: Introductionmentioning
confidence: 99%